EXPERIENCE IN RISK ASSESSMENT OF UNDERGROUND CONSTRUCTION - Kaufman, L. L.; Lysikov, B. A.; Zapolova, K. I.; Syrachov, I. Zh. (Science and Transport Progress, 2010)
The article gives examples of underground construction of hydropower station inNepaland sewer tunnel in the USA. These projects pay attention to influence of geotechnical risks and their consequences.